"I Want to Do Things With Languages": A Male Karenni Refugee's Reconstructing Multilingual Capital. Issue 4 (3rd July 2016) - Duran, Chatwara Suwannamai
ABSTRACT: This article discusses how a male Karenni refugee in the United States has constructed multilingual capital along the way of his multiple movements across national borders. As a member of an ethnic minority group in three different countries (Burma, Thailand, and the United States), he has invested in learning multiple languages throughout the movements. Based on a two-year ethnographic study on the participant's multilingual practices, I argue that being multilingual is a fundamental part of his transnational identities, economic security, and agentive acts. His roles outside formal classroom settings as a language broker, refugee, and an ESL tutor have been shaped by a continuum, or horizontal relationship of languages. The study suggests the inclusion of adult students' transnational identity and multilingual practices outside a language classroom. In addition, a career that requires multilingual skills and transnational knowledge should be encouraged and created for newcomers.